Identifying Factors Causing Delays and Cost Overruns in Construction Projects in Colombia (2018)
Construction project delays and cost overruns represent a source of concern for project developers, potentially affecting project feasibility. Thus, it is important to determine the causes of these issues, especially in Colombia where such causes are not well understood. In this research, a literature review was performed to identify causes of time delays and cost overruns around the globe. Subsequently, a survey of project-development professionals in Colombia was carried out in order to ascertain, in their opinion, the significant factors leading to time and cost deviations. Lastly, a statistical significance analysis was reported using the influential factors determined in the previous two steps, in order to establish correlations among these and other aspects, including scale and project type, business size, among others, implementing statistical and computational tools. This paper demonstrates that inadequate planning and lack of integration among professionals are the most significant factors contributing to construction delays and cost overruns in Colombia.